A Model or a Symbol? Criminal IP Judicial Reforms of Taiwan under U.S. Special 301 - Chang, Tao-Chou (My University, 2013)
This research examines the criminal intellectual property (IP) judicial reforms of Taiwan under the U.S. Special 301 framework. These reforms targeted the sole intermediate appellate court specializing in IP, the Intellectual Property Court (IPC). Following twenty years of judicial reforms trying to raise criminal punishment against IP infringers, Taiwan finally established the IPC in 2008 and transferred jurisdiction over appellate criminal IP cases to it. Due in part to these twenty years of reforms, the United States lifted its long-term Special 301 oversight from Taiwan in 2009, and named Taiwan as a successful model of fighting IP piracy. In spite of U.S. efforts, Taiwan's judiciary continued to follow existing sentencing patterns. This resistance to change appears to be due to the creation of a judicial culture surrounding the sentencing of criminal IP defendants and gradually increasing judicial independence in general. Because the institutional context within which judges sentence criminal IP defendants remained largely unchanged after the reforms, the reforms had little impact. Long-term conflicts between the reforms resulting from U.S. pressure and the local context of judicial practice were the reality behind what the United States claimed was a successful model of IP law reform to reduce piracy in Taiwan. The termination of the U.S. oversight in 2009 provides an opportunity to explore this so-called successful model. This research answers the following questions with respect to the conflicts: What is the U.S. Special 301 framework which shaped Taiwan's judicial reforms toward a punishment regime for IP protection? What are the contexts of Taiwan's judicial independence and judicial culture that protected and reinforced judges' existing sentencing patterns? How, and why, did the judiciary resist the pressure of judicial reforms toward a harsher punishment regime for IP infringement? This research outlines the legal framework within which the United States imposed pressure on Taiwan to reform its IP laws, evolution of Taiwan's IP laws during the period of intense U.S. pressure, and analysis of statistical data and individual cases with respect to judges' sentencing patterns before and after the establishment of the IPC. Based on these analyses, this research finds: (1) the rise of judicial independence following Taiwan's democratization blunted the impact of judicial reforms in the IP criminal sanctions area; (2) the long-term development of a local judicial culture reinforced the sentencing patterns favoring lenient sentences in the area of criminal IP law; and (3) in spite of the 2008 judicial reforms aiming to raise criminal punishment for IP protection there is no evidence to support the idea that judges changed their existing sentencing patterns and became harsher. In light of these findings, it appears that Taiwan cannot be held up as an example of success for the U.S. anti-piracy policy based on harsher criminal sanctions. In Taiwan, domestic judges' lenient sentences for IP infringements were unchanged by the judicial reforms under the U.S. Special 301 framework because growing judicial independence weakened the impact of the judicial reforms and within the judiciary local judicial culture reinforced the existing sentencing patterns.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: criminal sentencing; intellectual property piracy; judicial culture; judicial independence; Special 301; Taiwan; Law; Intellectual property; Asian studies; law